(untitled) (Research, Society and Development, 2020)
National and international surveys, such as performance indicators, demonstrate that the teaching process in Brazil is in a very worrying situation. However, it is in these difficult times that researchers must raise questions and propose solutions. Thus, this study comprises an analysis of the integration of alternative teaching tools, such as the virtual laboratory PhET, and action films with didactic characteristics, given the exclusive use of the expository method, in front of physics classes, for students from high school. Of a qualitative and quantitative nature, the investigation made use of questionnaires with conceptual questions to collect the data, applied at all stages and at the end of the cycle, aiming at making a comparative analysis of performance, either in the didactic sequences using the alternative resources, as only in which the lectures took place. The main results demonstrated that when alternative methodologies are used when teaching this natural science, the conceptual gain on the part of the students is greater than when there is only an expository and dialogued class. Concluding that in physics classes it is necessary to adopt different ways of exposing and working with the contents, and that educational software, and films, can be an effective resource.